(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examined the methods of performing ear amputation in dogs and the process of postoperative recovery. Amputation surgery is a complex process in which dogs are selected based on their ear anatomy, age, degree of injury, and general condition. During the study, various methods such as classical incision, V shaped incision, lobe (lateral oblique base), and cosmetic amputation were used, regularly observing the postoperative recovery process, decreased inflammatory symptoms, bleeding, and risk of infection.